PENGARUH ANTARA PRAKARYA, KEWIRAUSAHAAN, DAN PROSES PEMBELAJARAN TERHADAP SOFT SKILLS PESERTA DIDIK DI SMK NEGERI 01 KARANGANYAR TAHUN 2015/2016 - Giyanto Giyanto; Trisno Martono; Harini Harini (Department of Economics Education, Universitas Sebelas Maret, 2018)
The purpose of this study were (1) the effect of directly craft towards entrepreneurship, learning, and soft skills (2) the effect of direct entrepreneurship towards craft, learning, and soft skills (3) the effect of directly learning towards soft skills (4) the effect of indirectly craft and entrepreneurship towards soft skills. This research is quantitative descriptive method with correlation studies. Population and sample in this study were students of class X, XI, and XII Marketing Vocational high school 1 Karanganyar. Technique is simple random sampling. Data collection techniques used questionnaires and data analysis technique used path analysis.The results (1) A craft directly affect entrepreneurship 54%, on learning of 17%, and the soft skills of 34% (2) entrepreneurial directly affect the craft of 54%, on learning of 19%, and the soft skills of 10% (3) the learning process directly affects the soft skills of 3% (4) craft indirect effect on the soft skills of 1% and entrepreneurial indirect effect on the soft skills of 1%. Based on the findings, researchers recommend to learners and educators to be willing and able to learn by doing rather than just learning to know through direct practice.